Prosthetic Rehabilitation of Completely Edentulous Unrepaired Cleft Palate Patient with Implant Supported Hader Bar and Clips: A Case Report - Devkota, G; Joshi, SP; Shrestha, P; Sah, S; Verma, A (Journal of Nepalese Prosthodontic Society, 2022)
Prosthetic rehabilitation of an edentulous cleft lip and palate patient with a combined hard and soft palate defect is a great challenge, due to the lack of retention of the obturator prosthesis as a result of its weight and the inability to obtain a border seal. Dental implants improve the retention, stability, and occlusal function of prostheses when used in carefully selected cleft lip and palate cases. This clinical report presents an edentulous unilateral cleft lip and palate patient who has hard and soft palate defects and an atrophied maxilla, treated with an implant-supported speech-aid prosthesis Prosthetic rehabilitation of an edentulous cleft lip and palate patient with a combined hard and soft palate defect is a great challenge, due to the lack of retention of the obturator prosthesis as a result of its weight and the inability to obtain a border seal. Dental implants improve the retention, stability, and occlusal function of prostheses when used in carefully selected cleft lip and palate cases. The prosthetic rehabilitation of edentulous patient with unrepaired cleft palate poses a great challenge due to both hard and soft tissue defect compromising retention, support and stability of the obturator due to inability to obtain border seal and heavy weight. In carefully selected patient use of osseointegrated implant along with the bars and clips supporting and retaining maxillary overdentures on implants play a significant role in their efficacy. This clinical report presents an edentulous unilateral cleft palate patient treated with an implant-supported Hader bar and clips.